PERSEPSI WANITA USIA SUBUR TENTANG INSPEKSI VISUAL ASAM ASETAT (IVA)UNTUK DETEKSI DINI KANKER SERVIKS - Siregar, Debi Novita; Sartika, Dewi (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2019)
Cervical cancer is the second major cancer, after breast cancer, for childbearing age women. The are many new cases of cervical cancer in which 50% resulted in the patient death. Cervical cancer can be cured if detected quickly. IVA is a simple method that is able to be used for early detection in “Puskesmas”, relatively fast and accurate. The objectives of this study was to determine the perception of childbearing age women towards IVA for early detection of cervical cancer in “ Kelurahan Helvetia Tengah, Kecamatan Medan Helvetia. This research used qualitative design based on case study approach. There were 11 people samples (10 women of childbearing age and 1 person, a Helvetia health center employee. The results showed that the fertile women in Helvetia village had a positive perception about IVA for early detection of cervical cancer. However, they were reluctant to check IVA because afraid of the diseases. The conclusion is that clear information of IVA and cervical cancer is very important thing that should be understood by the childbearing age women.